2000
DOI: 10.1023/a:1008347630465
|View full text |Cite
|
Sign up to set email alerts
|

A phase I dose escalation study of the matrix metalloproteinase inhibitor BAY 12-9566 administered orally in patients with advanced solid tumours

Abstract: The recommended dose of BAY 12-9566 for further studies is 800 mg b.i.d. as this dose provides maximal plasma levels that can be achieved with a convenient dosing schedule for a chronically administered oral agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…In preclinical studies, growth inhibitory activity and reduction in the number of metastases were shown in various tumor models, with elevation of transaminase levels and mild depression of erythropoiesis as the principal toxic effects in animals [51][52][53][54]. Four phase I studies including a total of 89 patients have been performed [55][56][57][58][59]. Dose levels studied ranged from 100-1,600 mg/day.…”
Section: Phase I Studiesmentioning
confidence: 99%
“…In preclinical studies, growth inhibitory activity and reduction in the number of metastases were shown in various tumor models, with elevation of transaminase levels and mild depression of erythropoiesis as the principal toxic effects in animals [51][52][53][54]. Four phase I studies including a total of 89 patients have been performed [55][56][57][58][59]. Dose levels studied ranged from 100-1,600 mg/day.…”
Section: Phase I Studiesmentioning
confidence: 99%
“…However, as far as we are aware, no clinical trial has so far achieved satisfying results. Although chemical components, clinical trial design, and patient selection might be important factors, a better understanding of the role of MMPs in the pathophysiology of malignant tumors may be needed [4]. In this study, we measured the activity of MMP-2, -9 and -7 in tumor tissues of early-stage non-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%
“…Several agents have been developed that block the MMPs and prevent them from interacting with the molecules directing their activities to the cell surface or inhibiting their enzymatic activity. It can also be reduced indirectly, by inhibition of the signal-transduction pathways that induce MMP transcription by inhibiting tyrosine kinase receptor signaling [30-33]. …”
Section: Discussionmentioning
confidence: 99%